Preparation and characterization of Matrimid/P84 blend films - Qiu, Shuzhen (Kansas State University, 2014)
Polymeric membranes have been playing important roles in gas or liquid separations. Polyimide polymers are of interest due to their commercially availability along with good transport, thermal and mechanical properties. In this study, two common commercial polyimide polymers, Matrimid and P84 were blended, to combine the good transport property of Matrimid with the plasticization resistance of P84. Matrimid/P84 blend solutions ranging from 0-100 wt. % Matrimid were prepared to make blend films. Physical properties (density, d-spacing, thickness), transport properties (permeability of H2, N2, CH4, Ar, He, CO2, and gas pairs selectivity), thermal property (mass loss curves of TGA), and liquid solutes (water, methanol, toluene, butanol, 1-propanol, 2-propanol) desorption behavior were measured or characterized. Rules of changing behavior of the properties with mass fraction of Matrimid were investigated, summarized, and interpreted mathematically. As Matrimid mass fraction increases, there are more mobility and space between polymer chains, therefore there are smaller density, larger d-spacing, larger fractional free volume (FFV) and larger permeability. The selectivity-permeability relationship follows the trade-off line. Thermal mass loss curve of the blend films in air have presented intermediate characteristic with rising fraction of Matrimid compared to individual polymers. A partial-miscible behavior has been found from the correlation between permeability and FFV. The desorption behavior was found to be reasonably described by the case III model, where the diffusion rate is similar with relaxation rate of polymers.
Keywords: Chemical engineering; Matrimid; P84; Permeability; Desorption; Partial-miscible; Chemical Engineering (0542)